Analysis of socio-ethical ideas in Al-Farabi and Abay Kunanbaev’s works - Zhakipbek Altayev, Kazbek Raissov,; Petrik, James M.; Zhylkyshybaeva, Karlygash (Opción)
The study aims to investigate the analysis of socio-ethical ideas in Al-Farabi and Abay Kunanbaev’s works via comparative qualitative research methods. As a result, the enduring importance of Al-Farabi and A. Kunanbaev’s legacy is determined by the fact that many of their positions in the area of philosophy, sociology, logic, ethics, aesthetics, natural scientific ideas had a great influence on the subsequent development of social and philosophical thought of the people not only the East but also of Europe. In conclusion, the study of the political philosophy of al-Farabi acquires greater relevance in modern conditions strengthens harmony in society.